Eating disorders and disordered eating in athletes - Stoyel, H. (University College London, 2021)
Background: This research focusses on disordered eating and eating disorders (DE/ED) in athletes. DE/ED negatively impact athletes` physical and mental health and performance. Hence, understanding their development is key. Petrie and Greenleaf`s (2007) model is specific to athletes and served as a theoretical basis for this work. This model posits that initial predictors of disordered eating are sport pressure and societal pressure and describes several moderators and mediators. Aims and Methods: The thesis aimed to improve understanding of the development of DE/ED in athletes and develop a new model to predict DE/ED in athletes. The first task was to systematically review the evidence for Petrie and Greenleaf`s (2007) model. The next was to test the model`s applicability i na large cross-sectional sample. A qualitative study was undertaken to better understand the experiences of the athletes in the sample. Finally, a longitudinal study was conducted to test the model over time, using structural equation modelling and cross-lag mediation. Results: The systematic review yielded inconsistent findings, providing further support for the need to test Petrie and Greenleaf`s theoretical model. Testing their model in a large athlete sample revealed that it does not adequately explain DE/ED in athletes and a new model was developed that better fit the sample. This new model was then used in a longitudinal study, where it showed that societal pressures, mediated by internalisation, predicted later bulimic symptomatology. The qualitative study highlighted the complex interaction between societal expectations, social comparisons, and sport pressures that contribute to the development of disordered eating. Conclusions: These findings suggest that development and prevention of DE/ED in athletes may align with principles already established in research and practice for nonathlete populations. A key limitation was that the scales used were not reliable for athletes across time. Future research should include scales specifically designed for athletes.